Sustainability in Open Distance Learning (ODL) : adoption of market segmentation and advertising strategy / Mohd Nazri Mohd Noor ... [et.al.] - Mohd Noor, Mohd Nazri; Abdul Aziz, Azlina; Harun, Yanty Roslinda; Aminudin, Norsiah; Zakariah, Zulaikha; Satrya Wangsa, Ignasius Heri (Universiti Teknologi MARA Cawangan Sarawak, 2022)
The purpose of this paper is to examine the prospective learner’s perception of effective market segmentation and advertising messages for open distance learning (ODL) advertisements. A descriptive study was conducted to assess the perceptions of prospective ODL learners in Malaysia. Selfadministered questionnaires were used to obtain meaningful data from 314 respondents. The study was conducted from January to March, 2021. Based on the analysis, accessibility between the ODL institution and its market segments was viewed by the majority of the respondents as more important than substantiality. Furthermore, the respondents agreed that reminders and persuasive messages are significant in attracting audience attention to an ODL institution. The standardised path coefficients have shown that accessibility, reminders and persuasive messages are significant predictors of the sustainability of ODL institutions, whereas substantiality was perceived by the respondents as being insignificant.